On the critical mass of greenhouse gas - Klimchuk, E.F.; Tarasov, V.F. (Геофизический журнал, 2018)
In recent years, changes in the Earth’s climate have raised concern all around the globe. Climatologists have been drawing connections between global warming and a growing number of natural disasters, unexpected temperature fluctuations in some regions of the world and a number of other climatic aberrations. Within the scientific community, the opinions as to the nature and mechanism of the Earth’s climate change have split. Some contend that since the beginning of the industrial revolution, the carbon dioxide levels in the air have been steadily rising due to human production activities. Along with other gases, carbon dioxide has been inculpated for the greenhouse effect. In connection with this, a number of recent international conferences have adopted resolutions to reduce carbon dioxide emissions into the atmosphere. Another group of climatologists bases its findings on observations of solar activity, arguing that global warming is caused by a recurring spike in solar activity, with the current increase due to end soon, potentially giving way to a new ice age down the road. In the following work, we put forth yet another hypothesis regarding global warming. The influence of four main positive feedback loops caused by the secondary emission of water vapor, ÑÎ2, ÑÎ4, and decreased albedo on the earth climate system is shown on the basis of the general theory of feedback. If the present level of primary anthropogenic emissions of greenhouse gas (GhG) keeps, the total mass of atmospheric greenhouse gas can run up to such a critical value that the mentioned feedbacks, which give rise to self-amplification of the greenhouse effect, can cause the bifurcation transition of the climate system to the state of self-heating tending to the unlimited rise of mean temperature of the earth surface. В останні роки змінення клімату Землі непокоїть громадськість світу. Зростання стихійних лих, раптові температурні коливання в окремих регіонах світу та інші відхилення клімату від традиційної поведінки кліматологи пов'язують з глобальним потеплінням. Наукова громадськість з кліматології розділилася щодо питання механізму природи потепління клімату Землі. Одні дослідники вважають, що з моменту початку промислової революції виробнича діяльність людства з кожним роком збільшує кількість вуглекислого газу у повітрі. Як установлено, поряд з іншими газами він відповідає за парниковий ефект. У зв'язку з цим останнім часом відбулося кілька міжнародних конференцій, на яких ухвалено рішення про скорочення викидів вуглекислого газу в атмосферу.